Ecological Features of Small Mammal Populations in the Lower Reaches of the Amu Darya (Texas Journal of Multidisciplinary Studies, 2022)
The structural-temporal organization of the community of mouse-like rodents in the conditions of the lower reaches of the Amu Darya has been studied. It is shown that the long-term dynamics of community diversity indices is more associated with a change in the structure of dominance than with the dynamics of the number of species.